Assessing the Merger of Online Platform Companies: Does it Lead to Monopoly or just Business Expansion? (Analysis of The Merged Company of GoTo) - Sukarmi, Sukarmi; Al-Fatih, Sholahuddin; Tejomurti, Kukuh; Alam, Moch. Zairul (Jurnal Cita Hukum, 2021)
Two large digital platform companies, Gojek and Tokopedia, officially merged to form a holding company called the GoTo Group that is considered to have anti-competitive behavior and potentially data monopoly. This article aimed to analyze the adequate response to potential violations of the Prohibition of Monopolistic Practices and Unfair Business Competition Regulation and legal issues related to consumer data monopoly issues. This article uses normative legal research with the conceptual research and statute approach. The result shows that it is necessary to define “relevant markets” and the “substituted products” to determine the existence of unfair business competition in the Gojek-Tokopedia merger. It requires analyzing the consumer behavior in other marketplaces other than Tokopedia; when consumers do not "run" to Gojek, it means they are not in the same market. To prevent privacy protection failures in post-merger data integration, companies need to assess data sharing that may be carried out as part of a risk assessment. Regarding the rights of data subjects, The company needs to provide notification to the data subject regarding the Merger and Acquisition (M & A) given the data subject's right to refuse and guarantee that the M & A process will not violate the right to privacy of the customer's dataKeywords: Competition Law; Digital Platform; Merger Menilai Penggabungan Perusahaan Platform Online: Apakah Mengakibatkan Monopoli atau Hanya Ekspansi Bisnis? (Analisis Penggabungan GoTo)AbstrakDua perusahaan platform digital besar, Gojek dan Tokopedia, resmi bergabung membentuk holding company bernama GoTo Group yang dinilai memiliki perilaku anti persaingan dan berpotensi monopoli data. Artikel ini bertujuan untuk menganalisis respon yang memadai terhadap potensi pelanggaran Peraturan Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat serta masalah hukum terkait masalah monopoli data konsumen. Artikel ini menggunakan penelitian hukum normatif dengan pendekatan penelitian konseptual dan undang-undang. Hasil penelitian menunjukkan perlunya mendefinisikan “pasar relevan” dan “produk substitusi” untuk mengetahui adanya persaingan usaha tidak sehat dalam merger Gojek-Tokopedia. Hal ini membutuhkan analisis perilaku konsumen di pasar lain selain Tokopedia; ketika konsumen tidak “lari” ke Gojek, berarti mereka tidak berada di pasar yang sama. Untuk mencegah kegagalan perlindungan privasi dalam integrasi data pasca-merger, perusahaan perlu menilai pembagian data yang mungkin dilakukan sebagai bagian dari penilaian risiko. Mengenai hak subjek data, Perusahaan perlu memberikan pemberitahuan kepada subjek data mengenai Merger dan Akuisisi (M&A) mengingat hak subjek data untuk menolak dan menjamin bahwa proses M&A tidak akan melanggar hak privasi data pelangganKata Kunci: Hukum Persaingan Usaha; Platform Digital; PenggabunganОценка слияний компаний онлайн-платформ: приведет ли это к монополии или просто к расширению бизнеса? (Анализ слияний GoTo (Gojek и Tokopedia)  АннотацияДве крупные компании, занимающиеся цифровыми платформами, Gojek и Tokopedia, официально объединили свои усилия, чтобы сформировать холдинговую компанию GoTo Group, которая, как считается, ведет антиконкурентную политику и может монополизировать данные. Данная статья направлена на анализ адекватного реагирования на возможные нарушения Положения о запрещении монополистической практики и недобросовестной конкуренции, а также на правовые вопросы, связанные с проблемой монополии на данные потребителей. В данной статье используется нормативно-правовое исследование с концептуальным и правовым исследовательским подходом. Результаты исследования указывают на необходимость определить «соответствующие рынки» и «продукты-заменители», чтобы определить наличие недобросовестной деловой конкуренции в слиянии Gojek-Tokopedia. Это требует анализа поведения потребителей на рынках, отличных от Tokopedia; когда потребители не «бегут» в Gojek, это означает, что они не находятся на одинаковом рынке. Чтобы предотвратить сбои в защите конфиденциальности при интеграции данных после слияния, компаниям необходимо оценить возможное совместное использование данных в рамках оценки рисков. Что касается прав субъекта данных, Компания должна уведомить субъект данных о слиянии и поглощении (M&A), учитывая право субъекта данных отказаться и гарантировать, что процесс M&A не нарушит права на конфиденциальность данных клиента.Ключевые слова: Закон о деловой конкуренции; цифровые платформы; слияние